Mohelno – A terminal Last Glacial Maximum industry with microlithic tools made on carenoidal blanks. (25th June 2016) - Škrdla, Petr; Nejman, Ladislav; Bartík, Jaroslav; Rychtaříková, Tereza; Nikolajev, Pavel; Eigner, Jan; Nývltová Fišáková, Miriam; Novák, Jan; Polanská, Michaela
Abstract: Mohelno-Plevovce is a recently discovered Epigravettian site in the Czech-Moravian Highlands dated to the Last Glacial Maximum. The site is located on the shores of a water reservoir and remains of human habitation are continually eroding due to constantly fluctuating water levels. Several aspects of this site are notably unique in this region, including two stone structures interpreted as floor pavements of dwelling structures and microlithic implements. These particular microliths are previously unknown in this region, but they are very similar to other assemblages in distant parts of Europe. Raw materials for lithic artifacts associated with the stone structures were obtained locally as well as from distant sources up to 300 km from the site. Ochre, faunal remains and charcoal were also recovered and analyses of these remains indicate a cold, dry climate in an almost treeless landscape. Mohelno-Plevovce represents a rare insight into human habitation of a very sparsely populated central Europe during the LGM.